(untitled) (Minerva, 2020)
Study of the satire 1,9 of Horace and the imitatio that Leandro Fernández de Moratín offers in the dialogue “Ayer salí de mi casa”. The article explains against whom Moratín’s criticisms are directed. Moratín used the classic model of the Horatian satire to reject the new poetry by the pedantic and the copla composers, through deriding them and by applying moral and literary critique. This article argues that the copla composer who pursues Moratín is a reference to Francisco Mariano Nifo.